Neurophysiological and cognitive effects of Transcranial Direct Current Stimulation in three girls with Rett Syndrome with chronic language impairments. (May 2018) - Fabio, Rosa Angela; Gangemi, Antonio; Capri, Tindara; Budden, Sarojini; Falzone, Alessandra
Abstract: Background: this study was based on both neurophysiological decelerated activity and communication deficits in Rett Syndrome (RTT). Aims: the aim was to examine the neurophysiological and cognitive effects of Transcranial Direct Current Stimulation (tDCS) in three girls with RTT with chronic language impairments. Methods and procedures: we proposed an integrated intervention: tDCS and cognitive empowerment applied to language in order to enhance speech production (new functional sounds and new words). Because maximal gains usually are achieved when tDCS is coupled with behavioral training, we applied tDCS stimulation on Broca's area together with linguistic training. Outcomes and results: the results indicated a general enhancement in language abilities (an increase in the number of vowel/consonant sounds and words and the production and comprehension through discrimination), motor coordination (functional movements), and neurophysiological parameters (an increase in the frequency and power of alpha, beta and theta bands). Conclusion and implications: we assume that tDCS stimulation combined with the cognitive empowerment applied to language can significantly influence a chronic impairment even in genetic syndromes. Our results provide data that support the role of tDCS in fostering brain plasticity and in particular in empowering speech production and comprehension in girls with RTT.